#### Answer

-1

#### Work Step by Step

We are given that $a=-3$, $b=64$, and $c=6$.
Therefore, $\sqrt b-c+a=\sqrt 64-6+(-3)=8-6-3=2-3=-1$.
We know that $\sqrt 64=8$, because $8^{2}=64$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.